Effects of Q-Switched Laser Treatments on Acquired Bilateral Nevus of Ota-Like Macules: A Retrospective Comparative Study - Zeng, Rong; Liu, Yu-Zhen; Lin, Tong; Guo, Li-Fang; Ge, Yi-Ping; Zhang, Meng-Li; Yang, Yin; Wu, Qiu-Ju; Wu, Yu-Le; Li, Min (International journal of dermatology and venereology, 2019)
Objective:. Q-switched lasers, including 1064-nm Nd:YAG nanosecond laser (QSNYL), 755-nm alexandrite nanosecond laser (QSAL), and 694-nm nanosecond ruby laser (QSRL), are clinically available for the treatment of acquired bilateral nevus of Ota-like macules (ABNOM). However, no reliable evidence from large-scale comparative studies identifies which type of laser works best. This study aims to determine the differences in the effectiveness, complications, and risk factors of QSNYL, QSAL, and QSRL in the treatment of ABNOM, further to provide evidence for clinician to make optimal choice according to the condition of patients. Methods:. We collected the data from 685 ABNOM patients, including clinical features, medical treatments, and follow-up, since 1999 to 2014. The Kruskal–Wallis test was used to compare therapeutic differences between the three groups. The risk factors were analyzed using univariate analysis (χ2 test) and multivariate logistic regression analysis. Results:. The overall treatment efficiency of the QSNYL group (52.5%) and QSAL group (51.9%) was higher than that of the QSRL group (39.5%) (χ2 = 17.468, P < 0.001). The onset time of the QSRL and QSAL groups was shorter than that of the QSNYL group. The factors influencing efficacy in the QSNYL group were age at first treatment, number of treatments, coexistence with melasma, and the presence of hyperpigmentation; in the QSAL group was the number of treatments; and in the QSRL group was the number of treatments and hyperpigmentation. The prevalence of hyperpigmentation in the QSNYL group (30.5%) and the QSAL group (27.5%) was lower than that of the QSRL group (47.3%) (χ2 = 6.576, P < 0.001). Conclusion:. The QSNYL, QSAL, and QSRL are all effective and safe treatments for ABNOM. Considering the overall efficacy, duration of treatment, side effects, and risk factors, the QSAL is an optimal choice for ABNOM treatment.